Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.2165/00002018-199200071-00009
|View full text |Cite
|
Sign up to set email alerts
|

On the Possible Mechanisms and Predictability of Clozapine†-Induced Agranulocytosis

Abstract: Studies were conducted on serum removed from 15 patients before, during, and after, clozapine-induced agranulocytosis. Cytotoxic studies were compared with samples taken from patients during treatment with clozapine who did not develop agranulocytosis or treatment controls (TC); additional controls consisted of allogeneic (NC) and autogeneic serum from apparently normal people. The effect of serum on measurable functions of polymorphonuclear neutrophils (PMNs) taken from normal people was tested. Procedures un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
1
21
1
Order By: Relevance
“…Thus the mecha nism of clozapine-induced agranulocytosis has not been identified yet. although a factor cytotoxic to granulocytes has been isolated in the sera of patients with acute cloza pine-induced agranulocytosis [23], It has also been suggest ed that a particular clozapine metabolite, N-desmethylclozapine, may be responsible for this adverse reaction [24], In our study, agranulocytosis was observed in 3 out of 43 clozapine-treated patients (7%). The percentage is much higher than those quoted overall in the past 0.8% but lower than that reported by Lieberman et al [14] in Jewish patients (20%).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Thus the mecha nism of clozapine-induced agranulocytosis has not been identified yet. although a factor cytotoxic to granulocytes has been isolated in the sera of patients with acute cloza pine-induced agranulocytosis [23], It has also been suggest ed that a particular clozapine metabolite, N-desmethylclozapine, may be responsible for this adverse reaction [24], In our study, agranulocytosis was observed in 3 out of 43 clozapine-treated patients (7%). The percentage is much higher than those quoted overall in the past 0.8% but lower than that reported by Lieberman et al [14] in Jewish patients (20%).…”
Section: Discussionsupporting
confidence: 50%
“…As has been reported, drug-induced unwanted effects of the haematopoietic system are possibly due to immunolog ical reactions, drug toxicity including direct toxic effect of a drug or one of its metabolites, congenital metabolic defects as well as idiosyncratic reactions [20][21][22]. Thus the mecha nism of clozapine-induced agranulocytosis has not been identified yet.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of bone marrow toxicity from clozapine are still under debate. Toxic damage from clozapine or its metabolites (Veys et al, 1992) and immunological reactions (Pisciotta et al, 1992) are discussed. Recent studies demonstrate that clozapine probably impairs two stages of hematopoesis: damage to myeloblasts results in persisting agranulocytosis, toxic effects to late stages of granulocyte maturation result in granulocytopenia (Veys et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine and olanzapine bioactivation is thought to occur through a nitrenium ion [20]; however clozapine but not olanzapine induce toxicity to neutrophils. This can lead to an immune-mediated depletion of neutrophils and their precursors (CFU-GM) [21]. Also, nonsteroidal antiinflammatory drugs (NSAIDs) have pro-oxidant radicals that when metabolized could cause oxidative stress [22].…”
Section: Known Compounds With Hematotoxic Potentialmentioning
confidence: 99%